2017
DOI: 10.1080/10810730.2017.1290165
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Portrayal of Health Risk Behaviors by Black and White Characters in Popular Films

Abstract: Adolescent exposure to risk in film has been associated with behavior. We coded Black and White character involvement in sex, violence, alcohol use, and tobacco use, and combinations of those behaviors in popular mainstream and Black-oriented films (film n = 63, character n = 426). Health risk portrayals were common, with the majority of characters portraying at least one. Black characters were more likely than Whites to portray sex and alcohol use, while White characters were more likely to portray violence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In South Africa, there is a significant gap in socio-economic status (SES) between black and white populations, with a majority of black individuals falling within a low SES and whites in the high SES (68, 69). Previous studies have suggested that black individuals are more likely to drink and abuse alcohol (70), live a sedentary lifestyle (71,72) and have a higher prevalence of obesity (73,74) compared to white individuals. Black men were also reported to have a higher prevalence of smoking compared to white men (75,76), and a majority of older black women (aged 35 -65 years) were reported to consume more salt as compared to white women (77).…”
Section: Health Behavioursmentioning
confidence: 99%
“…In South Africa, there is a significant gap in socio-economic status (SES) between black and white populations, with a majority of black individuals falling within a low SES and whites in the high SES (68, 69). Previous studies have suggested that black individuals are more likely to drink and abuse alcohol (70), live a sedentary lifestyle (71,72) and have a higher prevalence of obesity (73,74) compared to white individuals. Black men were also reported to have a higher prevalence of smoking compared to white men (75,76), and a majority of older black women (aged 35 -65 years) were reported to consume more salt as compared to white women (77).…”
Section: Health Behavioursmentioning
confidence: 99%
“…Also, we chose to assess risky behavior and demographics of characters in the overall shows that appeared on both lists, but the small number of characters (n=27) was not ideal for group comparisons. The small number of Black characters (n=69) also made it prohibitive to determine if Black characters in shows that were popular with different groups had different rates of involvement in risk behaviors (this seems to be the case for movies, see Ellithorpe et al, 2017). While the content analysis was comprehensive in coding for the presence or absence of character involvement in numerous behaviors, contextual information (e.g., character approval/disapproval) as well as the nature and explicitness of the conduct were not considered.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 20.6% of sexually active adolescents drank alcohol before engaging in sexual intercourse (Centers for Disease Control and Prevention, 2015), and alcohol involvement prior to sexual intercourse is related to an increased risk for sexually transmitted infections (Santelli, Robin, Brener, & Lowry, 2001; Yan, Chiu, Stoesen, & Wang, 2007) and sexual assault (Abbey, 2002). Portrayals of behavioral combinations are also fairly common in movies and other media popular with youth (Bleakley, Romer, & Jamieson, 2014; Ellithorpe et al, 2017), and exposure to co-occurring alcohol and sex in television or movie content has been linked with adolescents’ intention to combine alcohol and sex (Bleakley, Ellithorpe, Hennessy, Khurana et al, 2017); (movies only; O’Hara, Gibbons, Li, Gerrard, & Sargent, 2013). Hence, it is important to consider television characters’ portrayal of both single and combined risk behaviors.…”
Section: Portrayal Of Health Risk Behaviors On Televisionmentioning
confidence: 99%
“…A content analysis of the films included in this sample reveals that Black characters were more likely to engage in sex and alcohol, compared to white characters who were more likely to be involved in violence (Ellithorpe et al, 2017). Black characters were also more likely to portray multiple risk behaviors, with sex and alcohol being the most common combination.…”
mentioning
confidence: 99%
“…Black characters were also more likely to portray multiple risk behaviors, with sex and alcohol being the most common combination. In the mainstream films, only 5.1% of characters were Black (75.3% were white, and 19.6% other) compared to 75.4% Black characters in Black-oriented films (20.9% white and 3.7% others) (see Ellithorpe et al, 2017). The underrepresentation of Black characters in popular media was also found in a comprehensive report of diversity in popular movies and television series, which concluded “the landscape of media content is still largely whitewashed”(Smith, Choueiti, & Pieper, 2016).…”
mentioning
confidence: 99%